Live, Online Short-Courses: A Case Study of Innovative Teacher Professional Development - Marrero, Meghan E.; Riccio, Jessica Fitzsimons; Woodruff, Karen A.; Schuster, Glen S. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
Teachers are searching for new venues through which they may meet stringent professional development requirements. Under competitive funding from NASA’s (National Aeronautics and Space Administration) Office of Education and the NASA Explorer Schools Project, U.S. Satellite Laboratory, Inc. created a series of live, online, interactive short-courses. In this case study, a mixed methods analysis of a variety of data sources reveals that diverse educators from a variety of classroom contexts view the short-courses as a useful professional development tool, both as a vehicle for a teacher’s own professional growth and for classroom applications. Teachers were particularly interested in the ability to participate in a collaborative community of practice with other educators, instructors, and scientists from across the country, and they found the flexible design of the professional development to be useful. This short-course design offers promise for future professional development opportunities.